Characteristics of organic acids in lacustrine organic-rich shale, Ordos Basin, China. (18th April 2019) - Yang, Fei; Xue, Lianhua; Yang, Shuang; Chen, Guojun; Bi, Guangxu; Lv, Chengfu; Ma, Ming; Su, Long; Zhang, Dongwei; Zhou, Qianshan
Abstract: Organic acids are critical to studying the formation of secondary porosity in tight lacustrine reservoirs, Ordos Basin. The expelled fluids produced through hydrocarbon evolution in a semi-closed system under different pressure and temperature settings (16.9 MPa, 250 °C; 22.1 MPa, 300 °C; 32.5 MPa, 350 °C; 37.7 MPa, 370 °C; 42.9 MPa, 400 °C; and 52.2 MPa, 450 °C) were collected. In this study, 12 different organic acids were identified using ion chromatography, and both the concentration and species of organic acids indicate a two-step process.